UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS ISLAM NUSANTARA DINOYO KOTA MALANG - Ning I’anatul Cholifah; Anwar Sa’dullah; Kukuh Santoso (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This research aims to describe the teachers efforts to increase students motivation on learning Islamic education at SMA Islam Nusantara. The study uses a qualitative research approach. Data collection techniques using observation techniques, interview techniques, and documentation techniques. The results of this study show how student motivation and teacher effort to improve the motivation to learn Islamic education and the constraints that occur when the teacher gives the students the cultivation.